Advances in Metal Halide Perovskite Memristors: A Review from a Co‐Design Perspective - Bowen Jiang; Xiang Chen; Xiaoxin Pan; Li Tao; Yuangqiang Huang; Jiahao Tang; Xiaoqing Li; Peixiong Wang; Guokun Ma; Jun Zhang; Hao Wang (Advanced Science)
Abstract The memristor has recently demonstrated considerable potential in the field of large‐scale data information processing. Metal halide perovskites (MHPs) have emerged as the leading contenders for memristors due to their sensitive optoelectronic response, low power consumption, and ability to be prepared at low temperatures. This work presents a comprehensive enumeration and analysis of the predominant research advancements in mechanisms of resistance switch (RS) behaviors in MHPs‐based memristors, along with a summary of useful characterization techniques. The impact of diverse optimization techniques on the functionality of perovskite memristors is examined and synthesized. Additionally, the potential of MHPs memristors in data processing, physical encryption devices, artificial synapses, and brain‐like computing advancement of MHPs memristors is evaluated. This review can prove a valuable reference point for the future development of perovskite memristors applications. In conclusion, the current challenges and prospects of MHPs‐based memristors are discussed in order to provide insights into potential avenues for the development of next‐generation information storage technologies and biomimetic applications.